IMPLEMENTASI LITERASI NUMERASI PADA PEMBELAJARAN MATEMATIKA KELAS V SDN 44 PADARIA MAROS - Abdul Muis; Suardi (STKIP Subang, 2026)
Abstract This study aims to provide an in-depth description of the implementation of numeracy literacy in the mathematics learning process for fifth-grade elementary school students. In addition, it seeks to identify the various factors that hinder the implementation of numeracy literacy, including those related to students, teachers, and the learning environment. Furthermore, the study examines the efforts made by teachers and schools to overcome these obstacles so that the implementation of numeracy literacy can be carried out optimally and effectively enhance students' mathematical thinking skills.